ON SCIENTIﬁ C AND MEDICAL PERSONNEL TRAINING AT V.I. SHUMAKOV NATIONAL MEDICAL RESEARCH CENTER OF TRANSPLANTOLOGY AND ARTIﬁ CIAL ORGANS OF THE MINISTRY OF HEALTHCARE OF THE RUSSIAN FEDERATION - artiсle Editorial (Вестник трансплантологии и искусственных органов)
.